Analytical determination of concentric carbon gradients within stable soil aggregates = Détermination analytique de gradients concentriques de carbone au sein d’agrégats stables de sol - Paul, Eldor A., author; Smucker, Alvin J. M., author; [ISSS-AISS-IBG-SICS], publisher (Colorado State University. Libraries, 1998)
Soil aggregation dynamics directly control agricultural production and reduce environmental contamination by convection-dispersion sequestrations of most ions. Greater containment and longer residence times of most plant nutrients, pesticides, and water would better sustain most agricultural production systems without polluting nearby groundwater supplies. In short, the large surface areas associated with the plethora of porosities within each natural soil aggregate provide dynamically interactive areas for chemical sequestration. Once known, it is these active/inactive centers which can be modified to improve plant productivity and water quality.
Détermination analytique de gradients concentriques de carbone au sein d’agrégats stables de sol
Workshop given at the 16th World Congress of Soil Science, Montpellier, France 20-26 August, 1998.
Scientific registration: 2742, Workshop: D, Presentation: oral.
Keywords: microgradients; delta 13C; mass spectroscopy